The Systematic Identification and Articulation of Content Standards and Benchmarks. Update - Kendall, John S.; Marzano, Robert J.; Mid-Continent Regional Educational Lab., Aurora, CO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This update addresses major issues surrounding educational standards for all subject areas. It provides a review and analysis of standards and benchmarks in the content areas of science, mathematics, history, geography, reading, and writing. Also included is an analysis and description of the knowledge and skills considered important for the workplace. Following the introductory section on the movement for national standards, the second section provides an overview of current standards-development efforts across subject areas. Section 3 describes in greater detail the technical and conceptual differences apparent since the beginning of the standards movement and the model of standards and benchmarks adopted for this study. Section 4 presents key questions that should be addressed by schools and districts considering a standards-based strategy. Section 5 describes the overall process used to identify standards and benchmarks, and Section 6 lays out the format and citation strategy used in the standard sections. Sections 7 through 15 provide the standards and benchmarks for nine separate areas. Appendixes list declarative and procedural knowledge structures by levels of generality. (Contains 54 references.) (SLD)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RP91002005.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Benchmarking; Criteria; Educational Assessment; Educational Change; Elementary Secondary Education; Geography; History; Identification; Job Skills; Mathematics; Models; National Competency Tests; Reading; Sciences; Standard Setting; Standards; Writing (Composition); Subject Content Knowledge; Reports, Evaluative; Information Analyses